Applications of Electrochemistry and Nanotechnology in Biology and Medicine I - Eliaz, Noam (Modern Aspects of Electrochemistry, 2011)
The study of electrochemical nanotechnology has emerged as researchers apply electrochemistry to nanoscience and nanotechnology. Containing recent breakthroughs, this is the first book of edited reviews of electrochemical applications in biology and medicine.